(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
The article describes the possibility of using physiotherapeutic methods of treatment in complex therapy, in particular intrauterine electrophoresis. The given method allows to improve the results of treatment of patients with panaritium, because against the background of the body’s reactivity changed by electric current, the adsorption properties of tissues increase, and ions are released from the connection with proteins and enter an active state. With the help of electrophoresis, it is possible to bring the drug directly to the pathological focus, which allows creating a high concentration in the affected area in the presence of capillary stasis, infiltration and necrosis. During the electrophoresis of drugs, no adverse reactions are observed, there is no pain, the integrity of the skin is not violated, the introduction of solvents and ballast substances is excluded, which helps to achieve the best effect in treatment with the least load on the patient’s body. drugs in the complex treatment of panaritium turned out to be more effective in comparison with the traditional scheme of treatment. Already after two or three procedures, patients’ general well-being and sleep improved, pain subsided, swelling and redness of the skin in the pathological area decreased, manipulations during bandaging became less painful, and the amount of purulent discharge decreased. The panaritium treatment method used by us made it possible to reduce the consumption of medicines by 25%. This fact, as well as the fact that the length of hospitalization in the experimental group was reduced (by an average of three days), indicate a significant economic effect of the use of intra-tissue electrophoresis in the treatment of purulent-necrotic lesions of the soft tissues of the upper extremities.